Analysis of the Significant Factors on Nurse's Performance in the Ward at the Doctor Soepraoen Hospital Malang - Dwi Anna Wahyuningrum (Journal for Quality in Public Health, 2020)
Nurse performance has an important role in healthcare and the continuity of hospital operations. For this reason, sufficient information is needed about the nurses requirements and the factors that influence them. Purpose of this study was to infestigate factors that were examined about the performance of nurses in the ward of Dr. Soepraoen Hospital. This is a quantitative study with a cross sectional design, which aims to measure independent variables and be approved at one time. The study sample was 166 nurses, using a questionnaire. Results showed that the most dominant factor had a comparison of the performance of nurses with β values of 0.76, work environment 0.51, and leadership 0.21. Simultaneously in the regression model, research, research, compensation, variables, compensation, coefficient of 0.81, work environment participation of 0.09 and leadership - 00.6. Researchers like a fairer compensation system through remuneration in order to motivate nurses to improve performance that will improve patient satisfaction in Dr. Soperaoen Hospital. These results indicate that there are differences between leadership, compensation and environmental variables with nurse performance, this means, facts that need attention from the hospital management to be able to improve nurse performance. The most dominant factor towards nurse performance is compensation, the expected system of recitation, incentives and honorariums have the greatest leverage in an effort to improve the performance of nurses in the inpatient care room of the Soepraoen Hospital Malang